Literatura afro-brasileira para crianças: os mundos de Tayó e Lukenya - Fior, Marcela Morais Dal (2021)
Our research aims to analyze how Afro-Brazilian literature for children contributes to the teaching and comprehension of Education of Ethnic-Racial Relations (EERR), in order to enhance a new relationship of identity belonging. We seek to contribute to new perceptions and points of view about Afro-Brazilian literature for children, as well as providing other ways to link literature and EERR and show the importance of building an anti-racist literary education from childhood. We know that literature has a humanizing dimension and this can enable the construction of anti-racist education. Thus, we carried out a literary analysis with books written by black authors, aimed at children: Kiusam de Oliveira with “The World in Tayó's Black Power” (2013) and Odara Dèlé with “Lukenya and its Poder Poderoso” (2019), written after the enactment of Law 10.639/2003. We theoretically base ourselves on the reflections proposed by Antônio Candido (2017) to talk about the relationship between literature and society; Eduardo de Assis Duarte (2010) in order to dialogue about the place of Afro-Brazilian literature. We also based on Regina Zilberman (2003) to think about children's literature. For the discussions related to identity belonging, we used texts by Nilma Lino Gomes (2005) and Eliane Cavalleiro (2018) as a basis to comprehend education of ethnic-racial relations. We emphasize the importance of these books being read to and by all children, as well as the relevance of composing the collections of classrooms and school libraries, since literature expresses our cultural, artistic, political, and social existence and, when united with ethnic-racial issues, it expands the possibility of understanding our human condition.